Glucocerebrosidase gene mutation is a risk factor for early onset of Parkinson disease among Taiwanese - Yih‐Ru Wu; Chien‐Ming Chen; C.-Y. Chao; L.-S. Ro; Rong-Kuo Lyu; Kuo‐Hsuan Chang; G.-J. Lee-Chen (2007)
Background: Mutations in the glucocerebrosidase (GBA) gene have recently been identified as contributing to the development of Parkinson disease (PD) in Ashkenazi Jews. Methods: To investigate whether this finding can be confirmed in a Taiwanese population, we conducted a case control study in a cohort of 518 PD patients and 339 controls for the three common GBA mutations in Taiwan, L444P, RecNciI and R120W, using PCR restriction enzyme assay and DNA sequencing. Results: Heterozygous GBA mutations were detected in 16 PD patients (3.1%) and four controls (1.2%). Although this difference was not statistically significant (p = 0.0703), the average age at disease onset of the 16 PD patients (50.6 (12.3) years) was significantly younger than that of the total patient group (63.8 (10.5) years; p = 0.0007) and the non-carrier patient group (64.2 (10.2) years; p = 0.0005). After stratification by age, the frequency of mutation carriers was significantly higher for the early onset PD (EOPD, age at onset ⩽50 years) group than for age matched controls (12.9% vs 1.8%; p = 0.0335) and there was a trend towards an increased risk of the mutation carrier with EOPD (odds ratio 8.30; 95% CI 1.45 to 156.53). Clinically, all 16 patients carrying a GBA mutation presented with a typical parkinsonian phenotype and experienced a good or excellent response to levodopa. Conclusions: Mutations of the GBA gene may be associated with the development of EOPD in Taiwan.